THE NEURAL NETWORK METHOD CLASSIFICATION OF LITERARY TEXT FROM THE VIEWPOINT OF ITS GENRE IDENTIFICATION - Ekaterina Andreevna Kuchukova; Irina Andreevna Babenko; Natalia Grigorievna Gudieva; Safwat Chiad Al-Galda (Современная наука и инновации)
Digital technologies today allow processing a large number of literary sources in order to ensure the availability and preservation of historical heritage.